2001
DOI: 10.1080/09593332208618315
|View full text |Cite
|
Sign up to set email alerts
|

Methane Oxidation in Three Alberta Soils: Influence of Soil Parameters and Methane Flux Rates

Abstract: Current concern over the potentially negative impacts of climate change has brought attention to anthropogenic sources of methane, a primary greenhouse gas. Two such emission sources are methane leakage at heavy oil wells and sanitary landfills. At both of these sources, substantial quantities of methane could potentially be oxidised by methanotrophic microbes living in soils. Optimisation of this phenomenon may serve as an inexpensive technique for reducing methane emissions. Soil column and batch incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…Variation of oxidation potential of landfill cover is examined using data provided by Stein and Hettiaratchi, 36 who report a CH 4 oxidation rate of 20% at a flow rate of 400 g CH 4 (m 2 day) Ϫ1 . Sensitivity to an increase of 100% of the amount of CH 4 oxidized reduced overall GHG emissions by 10%.…”
Section: Uncertainty and Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Variation of oxidation potential of landfill cover is examined using data provided by Stein and Hettiaratchi, 36 who report a CH 4 oxidation rate of 20% at a flow rate of 400 g CH 4 (m 2 day) Ϫ1 . Sensitivity to an increase of 100% of the amount of CH 4 oxidized reduced overall GHG emissions by 10%.…”
Section: Uncertainty and Sensitivity Analysismentioning
confidence: 99%
“…35 An Alberta, Canada study suggested that the rate of oxidation is dependent on CH 4 flow rate, suggesting the value of k may influence oxidation. 36 EPA and IPCC (1996 and 2006) make the assumption of 10% oxidation using aerating covering material. Although this may seem low in light of the range suggested above, the more conservative estimate is prudent without sitespecific data.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Optimal ranges of gravimetric moisture contents to facilitate CH 4 oxidation depend on soil texture, but typically ranges from 11-28%, with upper and lower limits of ≤ 3-7% and ≥ 30-41% (Whalen et al 1990;Stein and Hettiaratchi 2001;.…”
Section: Factors Affecting Ch 4 Oxidationmentioning
confidence: 99%
“…15 CH 4 oxidation in soil takes place because of the presence of methanotrophic bacteria. These metabolize CH 4 into CO 2 through various complex biological pathways.…”
Section: Ch 4 Recovered and Incineratedmentioning
confidence: 99%